2021
DOI: 10.1002/jdd.12651
|View full text |Cite
|
Sign up to set email alerts
|

How witnessing rudeness can disrupt psycho‐motor performance of dental students

Abstract: Rude and disrespectful behaviors are ubiquitous and pervasive in the workplace. The purpose of this study was to examine the effects of witnessed rudeness on dental student psychomotor performance. Using an experimental, betweensubjects design, 71 2nd (Sophomore) year dental students witnessed either an experimental (rude) or control (neutral) condition in which a confederate lab manager interacted in a rude or neutral manner with a prospective lab assistant candidate. Students then performed a mock prosthodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The effects of episodic incivility in the medical field are also featured prominently in the incivility literature. For example, work by Johnson, Haerling, Yuwen, Van Huynh, & Le (2020) found that nursing groups exposed to a single incident of incivility failed to follow standard protocols for administering cardiopulmonary resuscitation (CPR), dental students displayed reduced psycho‐motor performance (Woolum et al., 2021), and medical professionals were more likely to display declines in procedural and diagnostic performance (Risken et al., 2015). Within the medical field, experimental research has demonstrated that a single instance of incivility can result in poorer performance and lower information‐sharing among medical staff (Katz et al., 2019; Risken et al., 2015), lower diagnostic accuracy in neonatal intensive care units (Risken et al., 2015) fewer helping behaviors and decreased team member communication (Risken et al., 2015), and serious errors in the performance of CPR (Johnson et al., 2020).…”
Section: Behavioral Reactions To Episodic Incivilitymentioning
confidence: 99%
“…The effects of episodic incivility in the medical field are also featured prominently in the incivility literature. For example, work by Johnson, Haerling, Yuwen, Van Huynh, & Le (2020) found that nursing groups exposed to a single incident of incivility failed to follow standard protocols for administering cardiopulmonary resuscitation (CPR), dental students displayed reduced psycho‐motor performance (Woolum et al., 2021), and medical professionals were more likely to display declines in procedural and diagnostic performance (Risken et al., 2015). Within the medical field, experimental research has demonstrated that a single instance of incivility can result in poorer performance and lower information‐sharing among medical staff (Katz et al., 2019; Risken et al., 2015), lower diagnostic accuracy in neonatal intensive care units (Risken et al., 2015) fewer helping behaviors and decreased team member communication (Risken et al., 2015), and serious errors in the performance of CPR (Johnson et al., 2020).…”
Section: Behavioral Reactions To Episodic Incivilitymentioning
confidence: 99%
“…Woolum and colleagues studied dental students who witnessed a lab manager in an unrelated and rude or pleasant interaction prior to a surgical task [ 71 ]. They found that those exposed to this rude interaction were cognitively depleted, performed significantly worse than those in the control condition, and made significantly more errors.…”
Section: Experimental Effects Of Incivilitymentioning
confidence: 99%
“…Goldberg and Grandey (2007) found that customer rudeness increased the number of subsequent task errors customer service representatives made, and recent work has found that rudeness can harm performance even in critical contexts like medical settings (B. Cooper et al, 2022;Riskin et al, 2015Riskin et al, , 2017Woolum et al, 2021). However, research on rudeness in organizations has focused almost exclusively on its impact on individual victims, leaving its impact on work teams largely unexplored (Schilpzand et al, 2016).…”
mentioning
confidence: 99%
“…Goldberg and Grandey (2007) found that customer rudeness increased the number of subsequent task errors customer service representatives made, and recent work has found that rudeness can harm performance even in critical contexts like medical settings (B. Cooper et al, 2022; Riskin et al, 2015, 2017; Woolum et al, 2021).…”
mentioning
confidence: 99%